Shared and Distinct Selfie Motivations between China and the U.S. and the Distinguishing Influence of Nationality and Cultural Dimensions. Issue 1 (2nd January 2023) - Lyu, Yuanwei; Holiday, Steven
ABSTRACT: Research on selfies frequently focuses on motivational antecedents to the practice. To date, however, little scholarship has examined national and cultural differences in selfie motivations. The present study undertakes an identification and exploration of selfie motivations across nationalities by surveying 350 individuals from both China and the United States (the U.S.) who engage in the practice of taking and sharing selfies. Through factor analysis, analyses of variance, and moderation analysis, this study identifies both unique and shared cross-national motivations between China and U.S. individuals, examines how the identified mutual motivations differ between countries, and investigates how the cultural dimensions of individualism and collectivism influence selfie motivations. Implications for a modern, global selfie culture are discussed as well as what the identified results may indicate about cultural dimensions within a contemporary digital culture.